2010
DOI: 10.1007/s13280-010-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

A Richer, Greener and Smaller Alpine World: Review and Projection of Warming-Induced Plant Cover Change in the Swedish Scandes

Abstract: Alpine plant life is proliferating, biodiversity is on the rise and the mountain world appears more productive and inviting than ever. Upper range margin rise of trees and low-altitude (boreal) plant species, expansion of alpine grasslands and dwarf-shrub heaths are the modal biotic adjustments during the past few decades, after a century of substantial climate warming in the Swedish Scandes. This course of biotic landscape evolution has reached historical dimensions and broken a multi-millennial trend of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 63 publications
4
61
1
1
Order By: Relevance
“…Thus, our result contradicts some earlier studies and predictions that amelioration of climatic conditions may lead to low-altitude species colonising higher altitude sites (Sundqvist et al 2008;Kullman 2010;Sommer et al 2010), even though our observations span 16-31 years. However, our results agree with other studies which found no increase of lowaltitude species (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, our result contradicts some earlier studies and predictions that amelioration of climatic conditions may lead to low-altitude species colonising higher altitude sites (Sundqvist et al 2008;Kullman 2010;Sommer et al 2010), even though our observations span 16-31 years. However, our results agree with other studies which found no increase of lowaltitude species (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…of species with a significant decrease b 3 0 2 7 9 2 0 a Low-altitude species consist of species with boreal, northern or other origin/distribution sensu Hultén (1950) b According to t tests, see Supplementary Information We found that despite relatively large changes in species composition and species richness at individual sites, the overall changes were relatively moderate. The ecosystems are likely to have high inertia as the open vegetation is dominated by slow-growing clonal species that buffer change (Callaghan et al 2002;Kullman 2010). However, assuming a lack of change might be too early.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions leave species with fewer options for shifting their ranges to compensate for changing temperature. Consistent with the contractions observed for several high-elevation mammal species, all sites with disappearing climates occur above 1500 m elevation [53,54].…”
Section: Discussionsupporting
confidence: 80%
“…This fact has implications both for modelling treeline responses to climate change and as evidence of the potential biodiversity loss that likely will involve the treeless alpine belt vegetation in mountain environments because of fragmentation and habitat loss (Theurillat and Guisan 2001;Dirnböck et al 2003;Kullman 2010). A treeline upward advance by 200-600 m has been estimated for the next 100 years in the Swedish mountain region: a climatically driven change that could cause a 75-85% of reduction of the alpine areas, with most of the remaining area being constituted by scree slopes and boulder fields (Moen et al 2004).…”
Section: Discussionmentioning
confidence: 99%